Interconnected buildings in the Old Town of AlUla and their social significance - Almodarra, Aljohara; Barański, Marek; Vernet, Apolline (Proceedings of the Seminar for Arabian Studies, 2025)
Many traditional Islamic towns exhibit a clear connection between their urban structure and the social groupings that define their communities. This complex relationship is fundamentally anchored in a strong sense of place as studies demonstrate that it is common for clusters of buildings to be inhabited by direct or extended family members. However, attempts to reconstruct this distinctive socio-spatial pattern pose a significant challenge in the case of abandoned historical urban centres, regardless of whether they have been deserted for just a few decades. The Multiscalar Documentation of Urban Dynamics (MuDUD) Project’ interdisciplinary research on the Old Town of AlUla in the Kingdom of Saudi Arabia serves as an example of a non-invasive and successful method for investigating the impact of social dynamics on architectural space. This paper delves into the subject by examining building archaeological data pertaining to clusters of residential buildings, which are physically interconnected through various architectural means, in addition to engaging in targeted interviews with former town inhabitants. Consequently, it explores the mechanisms behind the creation and transformation of clusters of buildings, offering a new perspective on the town’s historical context and urban dynamics through the ages, with a specific focus on the last two hundred years.